Vascular resection in pancreatic cancer - Luketina, Ruzica-Rosalia; Hackert, Thilo; Büchler, Markus W. (Indian journal of surgery, 2015)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive malignant tumors and represents the fifth most common cause of cancer-related deaths. It is associated with a poor prognosis, likely due to the tendency of the tumor for early local and distant spread. One of the major obstacles of effectively treating PDAC is the often late diagnosis. Among all options currently available for PDAC, surgical resection offers the only potential cure with 5-year survival rate of approximately 15-20 %. However, in the absence of metastatic disease, which precludes resection, assessment of vascular invasion is an important parameter for determining resectability for pancreatic cancer. The vascular involvement in patients with pancreatic carcinoma ranges between 21 and 64 %. Historically, vascular involvement has been considered a contraindication to resective cure. Meanwhile, the surgical approach of pancreatoduodenectomy (PD) combined with vascular resection and reconstruction has been widely applied in clinical practice to remove the tumor completely. Therefore, vascular invasion is no longer a surgical contraindication and the rate of surgical resection has greatly increased. Moreover, PD combined with vascular resection can account for 20 to 25 % of the total cases of PD surgery in a number of the larger pancreas treatment centers. The aim of this review is to provide an overview of management and outcome of vascular resection in PDAC surgery.
Gesehen am 03.06.2020